2020
DOI: 10.1016/j.ecolind.2019.105882
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of an invasive bryophyte on plant species richness using high resolution imaging spectroscopy

Abstract: from generalized partial least squares (gPLS) regression models trained with cover information from 266 field plots (3 m × 3 m). Models were calibrated using different data subsets, following a spatially blocked subsampling design. In addition, the relationship between C. introflexus fractional cover and plant species richness was evaluated using a subset of plot data. Fractional cover estimates from gPLS models resulted in R 2 values of 0.64 ± 0.17 and an RMSE of 0.14 ± 0.02 based on independent validation da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Furthermore, scarcely vegetated patches can also contribute to species numbers. For example, in harsh environments such as coastal dune ecosystems, many focal species are small and occur in a very fine mosaic pattern of bare sand and vegetation (e.g., Ewald et al, 2020). Such areas may face the risk of being masked even though making a notable contribution to the species numbers.…”
Section: High Contrast Land Surfaces Will Increase Spectral Variationmentioning
confidence: 99%
“…Furthermore, scarcely vegetated patches can also contribute to species numbers. For example, in harsh environments such as coastal dune ecosystems, many focal species are small and occur in a very fine mosaic pattern of bare sand and vegetation (e.g., Ewald et al, 2020). Such areas may face the risk of being masked even though making a notable contribution to the species numbers.…”
Section: High Contrast Land Surfaces Will Increase Spectral Variationmentioning
confidence: 99%
“…However, this result should not be neglected as it relates well to the use of remote sensing techniques for monitoring invasive alien plants across vast areas [64]. Many studies have demonstrated the capability of remote sensing approaches to detect invasive plant species and to map their distribution [65][66][67][68][69][70] and certainly the use of the Rao's Q heterogeneity index in anthropogenic landscapes could be a powerful method to identify those areas potentially more prone to biological invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Ecological studies have benefited from UAV-borne remote sensing technology, and its potential is thought to have revolutionized ecology and conservation [13], especially in developing countries where research and cost-effective monitoring schemes are urgently needed. However, high ecosystem complexity results in painstaking and costly fieldwork campaigns.…”
Section: Introductionmentioning
confidence: 99%